PENATAAN MANAJEMEN ADMINISTRASI MADRASAH DINIYYAH TARBIYATUL ULAA DEREPAN MENOREH SALAMAN MAGELANG - Ahmad Fatkhul Mujib; Nailatul Muna; Arina Millataka (khidmatan, 2021)
This community service program aims to implement the tri dharma of higher education and as a form of student learning about society. The service program carried out in Derepan Hamlet, Menoreh Village, Salaman District, focused on the management of Islamic education by structuring the administrative management of the Madrasah Diniyyah Tarbiyatul Ulaa institution as one of the educational institutions in Derepan Hamlet. This administrative management arrangement is expected to help Islamic educational institutions Madrasah diniyyah Tarbiyatul Ulaa to be orderly and well-organized so that the teaching and learning process at Madrasah diniyyah can run well and produce graduates who are competent in religious knowledge.